A Retrospective Study on Colistin Nephrotoxicity in Pediatric Onco-hematology Patients - Ghafur, Abdul; Gohel, Swati; PR, Vidyalakshmi; Raj, Revathy (Journal of Pediatric Infectious Diseases, 2015)
Background There are limited data on the safety of colistin in pediatric patients, especially from developing countries.Methods This is a retrospective analysis of pediatric patients with carbapenem-resistant gram-negative bacteremia treated with colistin from an onco-hematology center in India. Nephrotoxicity was assessed using the pRIFLE criteria.Results Out of the 21 patients treated with colistin, 13 received concomitant nephrotoxic agents. Mean dose of colistin used was 141,050 IU/kg colistin methane sulfonate (CMS; 4.23 mg/kg, colistin base activity [CBA] = 11.28 mg/kg CMS) in three divided doses and mean duration was 7.85 days. None of the patients in our study developed nephrotoxicity according to the pRIFLE criteria.Conclusion There was no colistin-induced nephrotoxicity in our case series.
Keywords: colistin; nephrotoxicity; CRGNB; carbapenem-resistant gram-negative bacteremia